Salient Issues in Marketing Analytics - Osuagwu, Linus (British Journal of Marketing Studies, 2022)
Citation: Linus Osuagwu  (2022) Salient Issues in Marketing Analytics, British Journal of Marketing Studies, Vol. 10, Issue 1, pp.32-46,Abstract: The paper utilized materials from relevant extant literature and cognate experience to discuss marketing analytics with regard to its tools, relationship with big data, applications and challenges, and proposes research direction in cognate areas. Specifically, the paper posits that marketing analytics has some salient issues such as equivocal conceptualizations, strong connections with big data, myriad of tools and applications, in addition to associated challenges. These stated salient issues may not be exhaustive enough to represent all the cognate issues associated with marketing analytics, especially in contemporary times. This is a major limitation of the paper which can be addressed in future research efforts. Therefore, relevant empirical research streams are suggested in the paper to investigate these salient and other cognate marketing analytics issues in different contexts, including sectors, business types, and countries. The insights from the paper are likely to have practical and theoretical implications and relevance for marketing managers, organizational researchers and data scientists, among others, regarding marketing analytics tools, applications, connections with big data, and implementation challenges.